2022
DOI: 10.1177/13540661221098218
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and legitimacy in global governance: an empirical study

Abstract: This article undertakes an empirical investigation of the relationship between structural inequalities and legitimacy beliefs in global governance. Normative theory often emphasises inequality as a major source of injustice in global politics, but we lack empirical research that examines the implications of inequality for legitimacy in concrete situations of global governance. This paper draws on large mixed-method survey evidence regarding inequality perceptions and legitimacy beliefs at the Internet Corporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…These non-results add to other research that has not observed consistent gender effects on international attitudes (Alesina and La Ferrara 2002;Brewer et al 2004;Edwards 2009;Jongen and Scholte 2022). An exception is Johnson (2011), who…”
Section: Gendersupporting
confidence: 44%
See 1 more Smart Citation
“…These non-results add to other research that has not observed consistent gender effects on international attitudes (Alesina and La Ferrara 2002;Brewer et al 2004;Edwards 2009;Jongen and Scholte 2022). An exception is Johnson (2011), who…”
Section: Gendersupporting
confidence: 44%
“…finds, using Asia Barometer Survey data, that women support the UN more than men; however, Dellmuth and Tallberg (2015), using World Values Survey data, do not replicate this significant effect. A study of the Internet Corporation for Assigned Names and Numbers (ICANN) shows that women on average see larger gender inequalities than men in that global governance institution, and find those hierarchies more problematic, but that these concerns have no association with their confidence in ICANN (Jongen and Scholte 2022).…”
Section: Fig 311 Citizen Confidence In Ios (Individually) By Gendermentioning
confidence: 99%
“…The effort indicates that they find the governance institution “worthy” of their resources and support (Bäckstrand et al, 2021). Jongen and Scholte (2022) point out that when actors have underlying faith in a ruling apparatus, they are more ready to participate in its processes. Participating in Side Events can be interpreted as an endorsement in action; event hosts are more likely to consider the UNFCCC a legitimate venue for governing global climate change.…”
Section: Nsa Deliberation and Legitimacy Of The Unfcccmentioning
confidence: 99%
“…A deeper structure of modernity is apparent with the pervasive power across polycentric governance of the Internet of a techno-rationalism that prioritizes instrumentalist problem-solving through engineering fixes. Moreover, structurally embedded hierarchies of influence pervade the many institutions of polycentric Internet governance: inter alia in respect of age, ethnicity/race, gender, North-South geopolitics, and English language (Jongen and Scholte 2021). These various underlying ordering principles can operate concurrently on the Internet, sometimes in relations of mutual reinforcement and sometimes in contradiction (Scholte 2020).…”
Section: Underlying Ordersmentioning
confidence: 99%